Strengthening Local Leadership Through Training and Mentoring Programs for "KSPPS Nusantara" Management - Syuhada'; Muhammad Pratama Ghoni Arta Prayogi; M. Kholilurrohman; Andalusia Fatrah Hoiron; Andani Saharah; M. Zukhal Kubro (Shof Journal of Social Impact, 2024)
The program "Strengthening Local Leadership through Training and Mentoring Programs for KSPPS Nusantara Management" aims to increase the leadership capacity of KSPPS Nusantara administrators in Sawo Dukun Village, Gresik. The focus of this service is strengthening the role of administrators in managing the organization effectively and being responsive to community needs. The subjects of service are the KSPPS Nusantara administrators, totaling 15 people. The methods used include training, mentoring and participatory evaluation. The activity stages include identifying needs, program planning, intensive training, ongoing mentoring, and evaluation of results. This approach is designed to maximize administrator participation in the learning process and implementation of leadership strategies. The results show significant improvements in leadership abilities, organizational management, and active board participation. This program has also succeeded in creating new awareness of the importance of community-based social transformation. These findings support the importance of empowerment programs based on participatory training in encouraging sustainable social change.